Causes and Performance Analysis of UBS Acquisition of Credit Suisse - Yang, Xiongao (Transactions on Economics, Business and Management Research, 2024)
This paper mainly studies the event causes and performance results of UBS’s acquisition of Credit Suisse Group in 2023. As an international financial institution, Credit Suisse Group suffered serious financial difficulties under the combined effects of external changes in the global economic situation, internal management problems, prominent public opinion pressure and other factors, and was finally acquired by UBS for about 3 billion Swiss francs in 2023. This paper aims to reveal the development path and performance changes of the acquiring bank by evaluating the profitability, revenue, Operating expenses, and changes in the number of shareholders and shares in various regions of the world before and after the acquisition of UBS. The results provide some diversified suggestions for post-acquisition development of financial institutions.